PRATIC: A soluble-boron-free, pressurized water cooled, SMR core benchmark - Vuiart Romain; Eustache Aimeric; Eveillard Sarah; Prulhière Géraud (EPJ Nuclear Sciences & Technologies)
Current nuclear reactor research is actively exploring small modular pressurized water reactors (PWRs), particularly soluble-boron-free (SBF) configurations. SBF designs utilize control rods and gadolinium-poisoned fuel rods to manage reactivity. Additionally, small modular reactors (SMRs) commonly integrate steel reflectors to minimize neutron leakage. However, the compactness of SMRs and the adoption of these technical solutions result in notable fluctuations in neutron flux within the core during normal cycle operation. Hence, comprehensive analysis is essential, especially concerning reactor performance under normal and accident conditions, the reliability of neutronics calculation assumptions, etc. Research into these issues requires reactor core neutronics benchmarks that are consistent with industrial concepts so that the analysis results can be applied to real reactors. In this context, this article introduces PRATIC, a SBF-PWR SMR core neutronics benchmark designed to match the global performances of industrial concepts. The development of PRATIC was conducted using a deterministic calculation scheme coupling the APOLLO2 and CRONOS2 codes. PRATIC features a thermal power of 350 MWth, an equilibrium cycle length of 1.9 years, and an average discharge burnup of about 34 GWd/t, while maintaining controlled power distributions. The article elaborates on the design assumptions for PRATIC, then details the reactor core and its equilibrium cycle. Access to the PRATIC modeling data is available via a GIT repository, accessible upon request via email at pratic@cea.fr.